Peran Suami Dalam Keikutsertaan Istri Dalam Menggunakan Alat Kontrasepsi Pada Masa Kebiasaan Baru - Siti Nurmaliza; Yulia Irvani Dewi; Herlina (STIKes Payung Negeri Pekanbaru, 2022)
High population growth is a major problem nationally. This phenomenon is also characterized by an increase in the number of family planning acceptors, and in the Family Planning program, husband's support has a very important influence in choosing and deciding the use of family planning especially during the new normal. Qualitative phenomenology with descriptive design. The research sample with 5 participants who selected by the inclusion criteria using purposive sampling technique. Data collection is done by semi-structured interviews based on research objectives. Data analysis using thematic analysis stages according to Collaizi. The results of the study identified 4 themes, namely: a) the form of support given to the wife when choosing family planning, b) the reasons for choosing family planning during the new normal, c) health protocol procedures when using family planning, d) the husband's expectations of family planning services during the pandemic. Husband actively plays the role and provides support in the participation of his wife in using contraception during the new normal. It’s hoped husband to be proactive in providing support and be a wife's motivation in using family planning devices during the new normal.